Drivers of the Underground Economy around the Millienium: A Long Term Look for the United States - Rajeev K. Goel; James W. Saunoris; Friedrich Schneider (Institute of Labor Economics (IZA), 2017)
This paper provides a long term analysis of the determinants of the shadow economy. Using data for the United States over the years 1870–2014 we examine economic and political factors driving the underground sector. Results show that among the economic factors, greater economic prosperity increased the shadow sector, while greater openness to trade and a bigger government reduced it, with the effects of inflation being statistically insignificant. Politically, the efficacy of presidential vetoes and the effect of congressional party homogeneity are statistically insignificant. Further, the U.S. shadow economy increased during both world wars, but was lower during the great depression. However, in the short run, the relationship between the shadow economy and its determinants exhibit some remarkable differences.
Keywords: H26; K42; 330; shadow economy; underground economy; determinants; taxation; inflation; openness; world war; great depression